THE EFFECT WORK FROM HOME REGULATIONS AND UNEMPLOYMENT RATE ON GOJEK DRIVER WELFARE ONLINE IN CITY OF SURABAYA - Arifin, Syamsul; Utomo, Priyo (2021)
Since its first appearance in China in December 2019, corona virus, also known as Covid 19, has spread fast to practically every corner of earth. At the end of March 2020, it had become epidemic in more than 200 countries in earth with total of infected patients above 800,000 people, Covid-19 was first labeled an epidemic by World Health Organization (WHO) at the end of January 2020. However, due to the virus's rapid spread over the worldwide, the WHO classified Corona Virus a pandemic.. Various ways of handling Covid-19, especially in the hero city of Surabaya, have been carried out starting from the making of policies. One of the methods used to implement social distancing is to work from home or